(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2020)
A field experiment was conducted at Chandipur of Keraniganj Upazilla in the district of Dhaka, Bangladesh to screen out the studied rice varieties of BR 3, BRRI dhan 28, Local BRRI dhan 29, and BRRI dhan 74 as influenced by the Rice Straw Compost – RSC, Mustard Meal – MM, and Trichocompost – TC (indigenous organic amendments), and elevated soil temperature of 3°C in relation to the growth and yield response of rice. The experiment was conducted using split plot design with elevated temperature in main plots and the different rates of organic amendments in subplots. The rates of organic amendments were 0. 4, 8 t ha-1 for RSC; 0, 3, 6 t ha-1 for MM; and 0, 2.5, 5 t ha-1 for TC. The soil temperature was raised by 3°C from the daily field temperature of 22-25°C. Grain and straw yields, 1000-grain weight, number of filled and fissured grains of rice were significantly (p≤0.05) enhanced with the increased rates of RSC, MM, and TC at elevated temperature of 3°C.The maximum grain (8.86 t ha-1) and straw (8.40 t ha-1) yields were recorded in the treatment RSC4HW26-28 and RSC8HW26-28, respectively in BRRI dhan 29 over control, which endorsed the lowest grain (3.42 t ha-1) and straw (2.68 t ha-1) yields. The RSC treatment was ranked first in order of the growth-yield and yield components (1000 – grain weight and No. of filled and fissured grain) of rice followed by MM and TC treatments. The aforesaid treatments were found to have significantly (p≤0.05) positive aftermath with the elevated soil temperature, regardless of rice varieties. Increased rice production by the elevated soil temperature might be due to the CO2 fertilization, which is a very important climatic issue at present day environment. Bangladesh J. Sci. Ind. Res.55(1), 53-64, 2020